Endorepellin laminin‐like globular 1/2 domains bind Ig3–5 of vascular endothelial growth factor (VEGF) receptor 2 and block pro‐angiogenic signaling by VEGFA in endothelial cells. (28th February 2013) - Willis, Chris D.; Poluzzi, Chiara; Mongiat, Maurizio; Iozzo, Renato V.
<x xml:space="preserve">Abstract</x> Endorepellin, a processed fragment of perlecan protein core, possesses anti‐angiogenic activity by antagonizing endothelial cells. Endorepellin contains three laminin G‐like (LG) domains and binds simultaneously to vascular endothelial growth factor receptor 2 (VEGFR2) and α2β1 integrin, resulting in dual receptor antagonism. Treatment of endothelial cells with endorepellin inhibits transcription of VEGFA, the natural ligand for VEGFR2, attenuating the pro‐survival and migratory activities of VEGFA/VEGFR2 signaling cascade. Here, we investigated the specific binding site of endorepellin within the ectodomain of VEGFR2. Full‐length endorepellin was not capable of displacing VEGFA binding from VEGFR2 and LG3 domain alone did not bind VEGFR2. This suggested different binding mechanisms of the extracellular Ig domains of VEGFR2. Therefore, we hypothesized that endorepellin would bind through its proximal LG1/2 domains to VEGFR2 in a different region than VEGFA. Indeed, we found that LG1/2 did not bind Ig1–3, but did bind with high affinity to Ig3–5, distal to the known VEGFA binding site, i.e. Ig2–3. These results support a role for endorepellin as an allosteric inhibitor of VEGFR2. Moreover, we found that LG1/2 blocked the rapid VEGFA activation of VEGFR2 at Tyr1175 in endothelial cells. In contrast, LG1/2 did not result in actin cytoskeletal disassembly in endothelial cells whereas LG3 alone did induce cytoskeletal collapse. However, LG1/2 did inhibit VEGFA‐dependent endothelial migration through fibrillar collagen I. These studies provide a mechanistic understanding of how the different LG domains of endorepellin signal in endothelial cells while serving as a template for protein design of receptor tyrosine kinase antagonists. Structured digital abstract Ig1-3 of VEGFR2 binds to VEGFA by filter binding (View interaction) Ig3-5 of VEGFR2 binds to Endorepellin LG1/2 by enzyme linked immunosorbent assay (View interaction) Ig1-3 of VEGFR2 binds to Endorepellin LG1/2 by filter binding (View Interaction: 1, 2) Endorepellin LG1/2 binds to Ig3-5 of VEGFR2 by anti bait coimmunoprecipitation (View interaction) [Structured digital abstract was added on 3 May 2013 after original online publication]